The oral microbiota and gestational diabetes mellitus - Corrêa, Jôice Dias; Faria, Giovanna Araújo; Fernandes, Leticia Ladeia (Frontiers in Clinical Diabetes and Healthcare, 2023)
Gestational diabetes mellitus (GDM) is one of the most frequent endocrine condition of pregnancy. GDM is associated with adverse pregnancy outcomes and play roles in pregnancy health. Studies have demonstrated the link between pathogenic periodontal bacteria with glycemic control and risk of diabetes. The objective of the current study was to conduct a mini review of the available literature on the potential changes in the oral microbiota of women with GDM. The review was conducted by two independent reviewers (LLF and JDC). Indexed electronic databases (PubMed/Medline, Cochrane Library, Web of Science and Scopus) were searched, including articles published in English and Portuguese. A manual search also was performed to identify co-related articles. The oral microbial community of pregnant women with GDM is unique from that of healthy pregnant women. Most of the alterations found in the oral microbiota of women with GDM point to a favoring of an inflammatory environment with high levels of bacteria associated with periodontitis (Prevotella, Treponema, anaerobic bacteria) and a depletion of bacteria associated with the maintenance of periodontal health (Firmicutes, Streptococcus, Leptotrichia). More well-designed studies differentiating between pregnant women with good oral health and those with periodontitis to ascertain which differences are due to GDM or periodontal condition.